BRAF mutations in conjunctival melanoma: investigation of incidence, clinicopathological features, prognosis and paired premalignant lesions. (24th March 2016) - Larsen, Ann‐Cathrine; Dahl, Christina; Dahmcke, Christina M.; Lade‐Keller, Johanne; Siersma, Volkert D.; Toft, Peter B.; Coupland, Sarah E.; Prause, Jan U.; Guldberg, Per; Heegaard, Steffen
Abstract: Purpose: To investigate incidence, clinicopathological features and prognosis of BRAF‐ mutated conjunctival melanoma in Denmark. Furthermore, to determine BRAF mutations in paired premalignant lesions and evaluate immunohistochemical BRAF V600E oncoprotein detection. Methods: Data from 139 patients with conjunctival melanoma (1960–2012) were collected. Archived conjunctival melanoma samples and premalignant lesions were analysed for BRAF mutations using droplet digital polymerase chain reaction (PCR). Results were associated with clinicopathological features and compared with BRAF V600E oncoprotein stainings. Results: The overall incidence of conjunctival melanoma (0.5 cases/1 000 000/year) increased during the study period with 0.13 cases/1 000 000/10 years. The increase comprised a higher proportion of patients aged >65 years, epibulbar tumours and tumours developed from a primary acquired melanosis with atypia. BRAF mutations were identified in 39 of 111 (35%) cases. The rate ratio of BRAF ‐mutated versus BRAF ‐wild‐type melanoma did not change over time. BRAF mutations were associated with T1 stage (p = 0.007), young age (p = 0.001), male gender (p = 0.02), sun‐exposed location (p = 0.01), mixed/non‐pigmented tumour colour (p = 0.02) and nevus origin (p = 0.005), but did not associate with prognosis. BRAF status in conjunctival melanoma and paired premalignant lesions corresponded in 19 of 20 cases. Immunohistochemistry detected BRAF V600E mutations with a sensitivity of 0.94 and a specificity of 1.00 in newer conjunctival melanoma samples (2000–2012, n = 47). Conclusion: The incidence of conjunctival melanoma increased in Denmark over 50 years. The proportion of BRAF ‐mutated conjunctival melanoma was constant. BRAF mutations were identified as early events in conjunctival melanoma, associated with a distinct clinicopathological profile, similar to BRAF ‐mutated cutaneous melanoma. Immunohistochemical detection of BRAF can be used to assess BRAF V600E mutations.